Indolyl-chalcone derivatives trigger apoptosis in cisplatin-resistant mesothelioma cells through aberrant tubulin polymerization and deregulation of microtubule-associated proteins - Steinlein, Sophia; Essmann, Frank; Ghilardi, Amanda Franceschini; Horn, Heike; Schüler, Julia; Hausser, Angelika; Sun, Lijun; Ott, German; Kalla, Claudia (Frontiers in Oncology, 2023)
Purpose: Malignant pleural mesothelioma (MPM) is a neoplasm with dismal prognosis and notorious resistance to the standard therapeutics cisplatin and pemetrexed. Chalcone derivatives are novel, efficacious anti-cancer agents with minimal toxicity and have, therefore, gained pharmaceutical interest. Here, we investigated the efficacy of CIT-026 and CIT-223, two novel indolyl-chalcones (CITs), to inhibit growth and viability of MPM cells and defined the mechanism by which the compounds induce cell death. Methods: The effects of CIT-026 and CIT-223 were analyzed in five MPM cell lines, using viability, immunofluorescence, real-time cell death monitoring, and tubulin polymerization assays, along with siRNA knockdown. Phospho-kinase arrays and immunoblotting were used to identify signaling molecules that contribute to cell death. Results: CIT-026 and CIT-223 were toxic in all cell lines at sub-micromolar concentrations, in particular in MPM cells resistant to cisplatin and pemetrexed, while normal fibroblasts were only modestly affected. Both CITs targeted tubulin polymerization via (1) direct interaction with tubulin and (2) phosphorylation of microtubule regulators STMN1, CRMP2 and WNK1. Formation of aberrant tubulin fibers caused abnormal spindle morphology, mitotic arrest and apoptosis. CIT activity was not reduced in CRMP2-negative and STMN1-silenced MPM cells, indicating that direct tubulin targeting is sufficient for toxic effects of CITs. Conclusion: CIT-026 and CIT-223 are highly effective inducers of tumor cell apoptosis by disrupting microtubule assembly, with only modest effects on non-malignant cells. CITs are potent anti-tumor agents against MPM cells, in particular cells resistant to standard therapeutics, and thus warrant further evaluation as potential small-molecule therapeutics in MPM.